2023
DOI: 10.1186/s40359-023-01334-9
|View full text |Cite
|
Sign up to set email alerts
|

Moderation modelling of COVID-19 digital health literacy and sense of coherence across subjective social class and age among university students in Ghana

Isaac Amoako,
Medina Srem-Sai,
Frank Quansah
et al.

Abstract: Background The study assessed the moderation modelling of digital health literacy and sense of coherence across subjective social class and age among university students in Ghana during the COVID-19 pandemic. Methods A total of 1160 students were conveniently sampled from two universities namely, the University of Education, Winneba and University of Cape Coast, using the descriptive cross-sectional survey design. Preliminary analysis was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
(107 reference statements)
1
1
0
Order By: Relevance
“…This finding underscores the relevance of age in the association between SoC and SWB. This result also suggests that SoC interventions targeted at improving SWB should carefully consider the age variable, as has been strongly communicated by Amoako et al [79].…”
Section: Discussionsupporting
confidence: 58%
“…This finding underscores the relevance of age in the association between SoC and SWB. This result also suggests that SoC interventions targeted at improving SWB should carefully consider the age variable, as has been strongly communicated by Amoako et al [79].…”
Section: Discussionsupporting
confidence: 58%
“…In Africa, and particularly, in Ghana, it has been observed that university students (and even pre-tertiary students) have the tendency to rate themselves on how well they see themselves relative to others ( 34 , 35 ). Previous studies on the SSS and mental health outcomes have reported that people’s impression of their social status affect their health and overall well-being ( 24 ).…”
Section: Introductionmentioning
confidence: 99%